Infantile intrathoracic large airway obstruction in a setting with a high prevalence of tuberculosis/HIV. (3rd April 2018) - Barnard, Benjamin Wybrand; Du Plessis, Anne-Marie; Goussard, Pierre; Pitcher, Richard Denys
Abstract: Background: There has been no detailed analysis of the cause of intrathoracic large airway obstruction in infants in a resource-limited environment with a high prevalence of pulmonary tuberculosis (PTB) and human immunodeficiency virus (HIV). Aim: To define the aetiology and severity of intrathoracic large airway obstruction in infants in a tertiary South African hospital with a high prevalence of PTB and HIV. Methods: A retrospective study of infants was conducted with computerised tomography (CT) evidence of intrathoracic large airway obstruction from 1 January 2011 to 31 May 2014. CT scans were evaluated for the cause, site and severity of airway narrowing, with severity stratified as 'mild' (<50%), 'moderate' (51–75%) or 'severe' (>75%). Results: Forty-four patients (28 males, 64%; median age 145 days, range 5–331), and 79 sites of attenuation were included. Vascular (22/44, 50%) and nodal (18/44, 41%) compressions accounted for over 90% of cases. Thirty-five patients (79.5%) had at least one site of moderate/severe attenuation, and 26 (59%) had multiple such sites. Adenopathy was the commonest cause of moderate/severe compression (18/35, 51%). All cases of nodal compression were of tuberculous origin. HIV-serology was recorded in 32 patients (73%), one of whom, with vascular compression, was HIV-infected. Half of the patients (11/22, 50%) with vascular compression had congenital abnormalities, most commonly cardiac anomalies (7/22, 32%). There were no synchronous vascular and nodal compressions. Conclusion: Infantile intrathoracic large airway obstruction where there is a high prevalence of PTB and HIV is characterised by its extrinsic aetiology, severity and multicentricity, with more than half of all moderate/severe obstructions being caused by tuberculous adenopathy.